Heat tolerance assessment and molecular diversity analysis of wheat (Triticum aestivum L.) genotypes using Heat Susceptibility Index (HSI) and SSR/STS markers - Rajitha, J N; Rajneesh, K; Manoj, K P; Rajesh, A; Mishra, C N; Upama, M (Plant Science Today, 2026)
This study was conducted during the Rabi season of 2020-21, aimed to assess the heat susceptibility and genetic diversity of 25 wheat genotypes under four distinct environmental conditions: timely sown conditions in LPU, Jalandhar, Punjab (E1) and ICAR-IIWBR, Karnal, Haryana (E2), as well as late sown conditions at both experimental sites i.e. E3 and E4 respectively. These genotypes, sourced from ICAR-IIWBR, Karnal, Haryana, were cultivated following an Alpha Lattice Design with two replications. The evaluation of heat susceptibility using heat susceptibility index (HSI) categorized the genotypes into two groups: tolerant and susceptible. Heat stress responses varied among genotypes and locations. At Jalandhar (L-1), DBW187, HD3298, HI1612, DBW303, PBW644, NIAW3170, HD3086, HD3118 and DBW88 showed tolerance, whereas DBW222, WB-2, DBW173, DBW90, PBW771, HD3043, HI1605 and HD3249 were susceptible. In contrast, DBW222, HD3086, DBW173, WB-2, DBW90, HI1605, DBW88, PBW771, HD3043, NIAW3170 and HD3249 were tolerant at Karnal (L-2), whereas DBW303, DBW187, HD3298, PBW644, HD3118 and HI1612 were susceptible. Across both locations, HD2967, WH1142, HD3171 and WH1270 consistently exhibited heat tolerance, while DBW71, K1317, WH1105 and HI1628 remained susceptible. Furthermore, an analysis of genetic diversity employing STS and SSR markers revealed a similarity range from 0.61 to 0.94, with an average similarity coefficient of 0.77. Remarkably, genotype pairs such as DBW187 and WH1270, HD3086 and WH1142, DBW173 and HD3298, as well as DBW90 and WH1105, exhibited the highest similarity index of 0.94. The construction of a dendrogram using NTSYS-pc software delineated four major clusters, each of which was further subdivided. This research underscores the significance of genetic diversity in plant breeding, as it provides breeders with a rich pool of genetic resources to develop improved varieties endowed with various stress-resistant traits.